IMPLEMENTASI ALOKASI DANA BAGI HASIL CUKAI HASIL TEMBAKAU (DBHCHT) DI JAWA TENGAH - Mursid Zuhri; Alfina Handayani (Badan Perencanaan Pembangunan, Penelitian dan Pengembangan Daerah Provinsi Jawa Tengah, 2015)
The aim of the research was to determine the implementatition of DBHCHT allocation in Central Java Province. This is evaluatif descriptive research that conducted in 2010. The result showed that Improvement value of DBHCHT allocation every year in accordance with Regulation of Finance Ministry Number 197/PMK.07/2009 based on the 5 criteria. The regulation is followed up with the Provision of Central Java Governor Number 73, 2009. These criteria are : the number of tobacco tax receipts, the Average of tobacco production for three years previously, the development of the social environments are measured by index numbers of human development, the level of DBHCHT absorption for two years previously and the eradication level of illegal cigerrete. The regions that received DBHCHT Allocation were accordance with the ranking calculation based on the two main parameters, there are cigarettes and tobacco production, eventhough there was percentage change in the amount received by each region.